THE INFLUENCE OF MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE MORALE ENERGY EQUITY EPIC SENGKANG PTY. LTD. - Damayanti, Susi; Taba, Idrus; Hakim, Haeriah (Accounting Profession Journal (APAJI), 2024)
This study was carried out to ascertain and examine the impact of employee motivation and work environment on morale of Energy Equity Epic Sengkang PTY. LTD. This research uses qualitative research methods. The research sources were obtained from primary data through interviews with four employees of Energy Equity Epic Sengkang PTY. LTD. And secondary data sourced from literature - literature related to the discussion. The findings of this study suggest that work environment and motivation at Energy Equity Epic Sengkang PTY. LTD. It's effective and has a good impact on staff morale.